PEMANFAATAN ZAT WARNA WORTEL (Daucus carota Linn) DALAM PEMBUATAN PEWARNA BIBIR BENTUK BATANG (LIPSTIK) - Yuni Andriani; Sri Soeryati; Dolih Gozali (Jurnal Ilmiah Farmasi, 2009)
ABSTRACTThe utilization of natural colorant in cosmetic dosage form, especially the colorant of carrot(Daucus carota Linn) in the preparation of lipstick colorant have been carried out. It can be knownfrom the research that the extract colorant of carrot had an orange color and stable during storagetimes. Lipstick formulation with various concentration of the root colorant (20, 30, and 40%),produced lipstick that had good physical stability during storage times, and it had orange up toreddish orange, safe to be used, and the formula especially with the carrot colorant of 30% wasmore favorable.Keywords: cosmetics, lipstick, natural colorant, -carotenoid, carrot